Development of Chicken Nuggets by Incorporation of Vegetables - K, Jadhav P; Lokhande, S M; Udachan, I S (Journal of Postharvest Technology, 2022)
Chicken nuggets are a popular convenience food enjoyed by people of all ages. However, concerns  about the nutritional content and overall healthfulness of these products have led to an increased  demand for healthier alternatives. This project focuses on the development of chicken nuggets that  are not only delicious but also fortified with the goodness of leafy vegetables, offering improved  nutritional value without compromising taste and texture. Chicken and fenugreek, raw materials,  were procured from a public market and given the essential pre-treatments like washing, grading,  and sorting. A 0.2% citric acid solution was applied to fenugreek leaves for 30 minutes. The  fenugreek was dried by applying sun-drying and tray-drying methods after being treated with citric  acid and other raw materials. First, boneless chicken breast was weighed, cleaned, and chopped  into 8mm small pieces. Further, it was ground to make breadcrumbs. Ground spices and dehydrated  vegetable powder were added to the mixture, and dough was made. Further, the dough was cut  into small pieces and dipped into the breadcrumbs. The product can be kept in the freezer at a  temperature of 0 to 4°C for up to two months to be used later. It should be cooled and packed in  polyethylene bags. Storage should be at -18°C. Sensory and nutritional analysis were done. Finally,  the product was checked for microbial safety and quality assurance. Various sensory attributes were  studied for fiber-rich chicken nuggets enriched with fenugreek powder. Sensory evaluation during  storage was done for over 45 days at room temperature. Sensory attributes such as appearance,  flavor, taste, and overall appropriateness showed a decreasing trend during the storage period.  Sensory attributes decreased during a storage period of 90 days. The developed chicken nuggets  were more acceptable till the 60th day, showing an overall acceptability of 8.2±0.21. The sensory  scores were least on the 90th day. The overall acceptability of the product on the 90th day was  7.8±0. The findings from this study may be invaluable to food technologists, researchers, and the  food industry, ultimately fostering innovation and encouraging the development of new, healthier  food products. As consumers continue to seek balanced and nutritious choices, the outcome of  this project can potentially influence the way chicken nuggets and similar products are formulated,  produced, and perceived in the market.
Keywords: Chemical analyses; chicken nuggets,; fenugreek powder.